Cytotoxic and anti-inflammatory effects of lignans and diterpenes from Cupressus macrocarpa. Issue 10 (15th May 2020) - Al-Sayed, Eman; Ke, Tzu-Yi; Hwang, Tsong-Long; Chen, Shu-Rong; Korinek, Michal; Chen, Shu-Li; Cheng, Yuan-Bin
Graphical abstract: Abstract: Cupressus macrocarpa is a windbreak tree and is reported to have various cytotoxic effects. A natural product study on the leaves of C. macrocarpa has yielded ten secondary metabolites, including three new diterpenoids (1 –3 ), four known diterpenoids (4 –7 ), and three known lignans (8 –10 ). The structures of all isolated compounds were elucidated via the interpretation of spectroscopic methods, especially 2D NMR and mass analyses. In the cytotoxic assays, compounds 1 –3 and 7 –10 showed inhibition effect against HepG2, MDA-MB-231, and A549 cells with IC50 values ranging from 0.004 to 19.9 μg/mL. Moreover, the anti-inflammatory assays revealed that (−)-matairesinol (8 ) had significant inhibitory activities on superoxide anion generation (IC50 = 2.7 ± 0.3 μM) and elastase release (IC50 = 6.6 ± 0.7 μM).